COVENANT IN THE OLD TESTAMENT (1983)
This Thesis is divided into six Chapters, preceded by the Preface. The Preface explains the concept of Covenant. It examines the Israelite faith from its rudimentary stage and its gradual development; and the relationship between the Israelite Covenant and the other peoples. Chapter One begins with the Introduction to the Thesis. It discusses the Covenant upon which the religion of Yahweh was based, and as the institution which established a unique relationship between God and Israel. Covenant, it explains, was enshrined in the Salvation history of the Israelites as a saving grace of God. It is therefore a gift made by Yahweh to Israel. The Chapter also examines the definition and etymology of Covenant. The Covenant in the Ancient world, especially, the structure of the Hittite treaties; and the terminologies of the Covenant in the Old Testament are looked into. Chapter Two is devoted to the Covenant forms in Israel, namely, the Secular traditions, the God-bound, and Israel bound Covenants, and the Covenant of Joshua. Chapter Three focuses attention on the physical aspects of the Covenant: Statutes, Instruments and Sacred objects. Chapter Four examines the nature of the Covenant God as an Ethical and Personal Being; the relationship between Him and Baal; the Covenant as a doctrine of Redemption, namely, the religious and saving consciousness of Israel; the motive to the formation of the covenant; and the justification of the Choice of Israel for the Covenant. The Chapter ends with a study of the Covenant people as a righteous people. Chapter Five is concentrated on the Deuteronomic reform; the idea of a new Covenant; Covenant breaking and judgment; the Covenant in Exilic period; and the Post-exilic impact on the Covenant. The Conclusion forms the first section of the last Chapter. It gives a concise account of the crucial views reached in this Thesis, especially in stressing the fundamentals and uniqueness of the Covenant theology. The Chapter concludes with the examination of the effect of covenant on the Israelites.